The factors contributing to the different self-sufficiency adaptation and academic performance: the case of international students at Malaysian public universities - Irma Wani Othman; Sabariah Mohd Rahim; Anna Lynn Abu Bakar (Global Academic Excellence, 2022)
Globalization has made it possible for international students to pursue their studies overseas. Malaysia is one of the leading destinations for these students to continue their studies, and this aligns with our vision to achieve the internationalization of higher education by the year 2025. This intense initiative has made our educational institutions recognized globally towards world prestigious educational hub. In relation to this, this article aims to analyze the international students' feedback on their experience in the self-sufficiency adapting process that has become the stakeholders' focus. The study uses the qualitative approach by utilizing the semi-structured interviews of 40 international students in the first year of their study in selected public universities. The findings of the study show a positive relationship between the students’ self-sufficiency and their academic performance. The factors contributing to the different self-sufficiency adaptation of the students were discussed in the context of the recognition for the public university’s reputation, current courses offered by the university, the courses’ marketability, English as the medium use in the university teaching delivery, customers’ satisfaction, and the guaranteed quality services coordination, and. continuous accreditation recognition. The findings will become valuable information for future international students planning to further their study overseas. The findings can also be used as guidelines by the university’s management in understanding the implication of self-sufficiency and sustainability on international students’ academic performance.